South Africa : Financial Sector Assessment Program-Technical Note on Systemic Risk Oversight and Macroprudential Policy. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
South Africa has made significant progress in strengthening its macroprudential policy framework and foundations since the 2014 FSAP. Institutional arrangements were overhauled by the 2017 Financial Sector Regulations Act that, among others, introduced the current 'Twin Peaks' structure, provided SARB with a strong financial stability mandate, and sought to foster interagency coordination and collaboration (including via the establishment of the Financial System Council of Regulators. As a result, South Africa has a hybrid macroprudential policy framework that combines a 'strong' decision maker in the SARB Governor, but that is importantly supported by an advisory committee structure, fostering effective cooperation and coordination. Systemic risk monitoring has also been enhanced and some macroprudential policy tools phased-inches
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; South Africa